Factors influencing disclosure among women experiencing intimate partner violence during pregnancy in Moshi Municipality, Tanzania. (December 2016) - Katiti, Victor; Sigalla, Geofrey; Rogathi, Jane; Manongi, Rachel; Mushi, Declare
Abstract Background Intimate Partner Violence (IPV) has serious negative health effects to millions of women around the globe. While disclosing IPV could open doors for support and eventually prevent partner abuse, the factors associated with IPV disclosure during pregnancy are not well known. The aim of this study was to examine factors influencing IPV disclosure to any person of interest or organization supporting women during pregnancy in Moshi Municipality, Tanzania. Methods Data were from a prospective cohort study of 1123 pregnant women followed-up by the project aiming to assess the impact of violence in the reproductive health conducted in Moshi Municipality, Tanzania from March 2014 to May 2015. Inclusion criteria to the current analysis were all 339 pregnant women who reported to have experienced physical, sexual and/or emotional violence during the index pregnancy. Data analysis used SPSS Version 20. Odds ratio with 95 % Confidence Interval (CI) for factors associated with IPV disclosure was estimated using multivariate logistic regression models while controlling for age, education and parity. A p-value of less than 0.05 was considered for a statistically significant difference. Results IPV disclosure was found to be 23.3 % (n  = 79). Disclosure of IPV was less likely among unemployed (OR = 0.5, 95 % CI 0.30–0.90) and women whose index pregnancy was unplanned (OR = 0.53, 95 % CI 0.29–0.98). Women who regularly participated in women's or community groups, religious groups or political associations at least once a month had 2 times higher odds of IPV disclosure compared to those who did not attend regularly (OR = 2.12, 95 % CI 1.13–3.95). Most of the abused women during pregnancy who disclosed their experience of IPV (69 %) disclosed to a member of the family of birth followed by friends (14 %) and a member of family of the partner (11 %). Conclusions Most of the women who experienced IPV during pregnancy kept suffering in silence while less than a quarter of all the abused (23.3 %) disclosed their experience to someone. Identification of the women experiencing IPV during pregnancy should be done as a starting point for supporting victim of IPV. Women empowerment in economical and reproductive health will reduce their vulnerability and facilitate disclosure of IPV for support. Key individuals who informally support victims of IPV should be targeted in interventions.